Drones in Insect Pest Management - Subramanian, K. S.; Pazhanivelan, S.; Srinivasan, G.; Santhi, R.; Sathiah, N. (Frontiers in Agronomy, 2021)
The insect pests are known to cause catastrophe and drastic reduction in food grain production across the globe. Such losses have been predicted by FAO is over 37% due to pests and diseases. Recently, the crops cultivated in India being threatened by invasive pests like fall army worm (Spodoptera frugiperda JE Smith) in maize and Rugose spiraling whitefly in coconut (Aleurodicus rugiperculatous Martin) have caused extensive damage during the year 2018 and 2019. The plant protection measures are to be taken as community basis so as to ensure effective management of pests. In India, more than 80% of the farm lands are in the category of small and marginal (< 1 ha), it is very difficult to manage the invasive pests. If one field is sprayed, the pests simply shift their feeding to the neighboring fields. To address this, drones become utmost essential. Drones are unmanned aerial vehicles widely exploited in a wide array of disciplines such defense, monitoring systems and disaster management but beginning to scratch the surface in agricultural sciences. There are three major types of drones encompassing fixed wing, multi-rotor and hybrid type and the usage depending on specific applications. The other types depend on degree of automation, size and weight besides power source. The set operational parameters such as flight speed, height and endurance are to be optimized to use it appropriately in agriculture and allied sectors. In addition, parameters related to drone based spraying viz., Droplet coverage, Droplet Density, Uniformity of the Deposition; Droplet Penetrability should also be factored in while implementing drone based mitigation strategies. Although many have explored crop pest management using drone technology, they have been limited to only a small area. The regulatory guidelines have been set across the globe to perform site-specific farm management with higher precision at very high resolution. Overall, drones can be employed in almost all agricultural field operations and are considered excellent tools for rapid, reliable and non-destructive way to detect the field problems. This review provides panoramic views of drone technology and its application in management of pests in digital agriculture era.